In vitro reprotoxicity of carboxyl‐functionalised single‐ and multi‐walled carbon nanotubes on human spermatozoa. (21st December 2016) - Aminzadeh, Z.; Jamalan, M.; Chupani, L.; Lenjannezhadian, H.; Ghaffari, M. A.; Aberomand, M.; Zeinali, M.
Summary: Reproductive toxicity of carboxyl‐functionalised carbon nanotubes (CNT‐COOH), as the most commonly used form of water‐soluble CNTs, is not clearly studied. The aim of this study was to investigate in vitro toxicity of carboxylated single‐walled and multi‐walled CNTs (SWCNT‐COOH and MWCNT‐COOH) against human spermatozoa. Sperm cells from healthy donors were incubated with 0.1–100 μg/ml of SWCNT‐COOH or MWCNT‐COOH at 37°C for up to 5 hr. Viability of sperm cells was assessed using MTT test, and sperm motility was evaluated following World Health Organization guideline. Production of reactive oxygen species (ROS) and nitric oxide (NO) in sperm was also assessed. We showed that both MWCNT‐COOH and SWCNT‐COOH following incubation in vitro with human spermatozoa did not exert negative effect on viability while motility was significantly ( p < .05) dropped in a dose‐dependent manner. Moreover, there was no significant effect of the type, dose and exposure time of the CNT‐COOH on NO production. Exposure of sperm cells to both examined types of CNTs at concentrations as low as 0.1 μg/ml caused a significant increase in ROS levels. In conclusion, carboxylated forms of CNTs seem to be harmful for human spermatozoa. Further studies, especially using in vivo models, are needed to decide about reprotoxicity of carboxylated forms of CNTs.